TANGGUNG JAWAB RUMAH SAKIT ATAS KELALAIAN TENAGA MEDIS DALAM PELAYANAN KESEHATAN - Dewi Harmoni; Fahmi Fahmi; Yetti Yetti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
Abstract: This article aims to find out how the hospitals’s legal responsibility for negligence of medical personnel in health services and the legal responsibility of medical personnel for negligence in hospital health services.Hospital is a health care institution that organizes individual health services in a plenary that provides inpatient, outpatient, and emergency services.Article 46 of the hospital law Number 44 of 2009 concerning hospitals explicitly stipulates that hospitals must be legally responsible for losses caused by health workers in hospitals,namely with the presence of a superior respondeat doctor,the hospital is responsibleresponsibility for the quality of care,and the doctrine of vicarious liability,hospital liability,corporate liability.The provisions regarding this responsibility must realy on articles 1367 of the civil code.medical personnel as one of the parties to the agreement by the hospital do have achievement in seeking patient healing through the search for the most appropriate therapy and not in promising healing from the patient he only does his best according to the knowledge and experience he has. Keywords: Hospital Responbility, Negligence, Medical Personnel Abstrak: Artikel ini bertujuan untuk mengetahui bagaimana tanggung jawab hukum Rumah Sakit atas kelalaian tenaga medis dalam pelayanan kesehatan dan tanggung jawab hukum tenaga medis aras kelalaian dalam pelayanan kesehatan di rumah sakit.Rumah Sakit adalah institusi pelayanan kesehatan yang menyelenggarakan pelayanan kesehatan perorangan secara paripurna yang menyediakan pelayanan rawat inap,rawat jalan,dan gawat darurat. Pasal 46 Undang-Undang Rumah Sakit Nomor 44 tahun 2009 Tentang Rumah Sakit secara eksplisit mengatur rumah sakit harus bertanggungjawab secara hukum atas semua kerugian yang ditimbulkan oleh tenaga kesehatan dalam rumah sakit yaitu dengan adanya doktrin respondeat superior, rumah sakit bertanggungjawab terhadap kualitas perawatan (duty to care),dan doktrin vicarious liability, hospital liability, corporate liability.Ketentuan mengenai tanggung jawab ini harus bertumpu pada Pasal 1367 KUHPerdata.Tenaga medis sebagai salah satu pihak dalam perjanjian oleh rumah sakit memang memiliki prestasi untuk mengupayakan penyembuhan pasien melalui pencarian terapi yang paling tepat dan bukan pada menjanjikan kesembuhan dari pasien. Oleh karena itu, tenaga medis memiliki tanggungjawab atas tindakan yang dilakukannya hanya sebatas upaya yang terbaik menurut ilmu pengetahuan dan pengalaman yang dimilikinya. Kata kunci: Tanggung Jawab Rumah Sakit, Kelalaian, Tenaga Medis.